2014
DOI: 10.1590/1806-9282.60.05.010
|View full text |Cite
|
Sign up to set email alerts
|

Reeducation of pelvic floor muscles in volleyball athletes

Abstract: Objective: to verify the effectiveness of the pelvic floor muscles rehabilitation program (PFMRP) in female volleyball athletes, analyzing the amount and frequency of urinary leakage. Methods: experimental study. The sample consisted of 32 female athletes from Famalicão Athletic Volleyball Club (Portugal). The athletes were selected by convenience and distributed randomly into two groups: experimental group (EG = 16 athletes) and the control group (CG = 16 athletes). The EG underwent PFMRP for three months. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
1
7

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(57 citation statements)
references
References 23 publications
0
45
1
7
Order By: Relevance
“…32 On the other hand, Yi et al 13 found that 24% of tri-athletes had at least one arm of the female athlete triad, but the athletic triad was not associated with symptoms of any pelvic floor disorders, for example, UI. Our results did not confirm other findings from other sports where low BMI 12,29 and length of participation in sport/hours of training 15,18,[33][34][35][36][37][38][39][40][41][42][43] were significant risk factors. This may be explained by the high training load and low BMI in all the rhythmic gymnasts.…”
Section: Discussioncontrasting
confidence: 99%
“…32 On the other hand, Yi et al 13 found that 24% of tri-athletes had at least one arm of the female athlete triad, but the athletic triad was not associated with symptoms of any pelvic floor disorders, for example, UI. Our results did not confirm other findings from other sports where low BMI 12,29 and length of participation in sport/hours of training 15,18,[33][34][35][36][37][38][39][40][41][42][43] were significant risk factors. This may be explained by the high training load and low BMI in all the rhythmic gymnasts.…”
Section: Discussioncontrasting
confidence: 99%
“…In relation to the type of UI, in studies by Ferreira et al [18], 32 volleyball athletes (100%) presented UI of effort; Reis et al [13] and Borin et al [17] observed effort-based UI among 30% and 19% of the volleyball athletes, respectively. From the 5 addressed articles, Nygaard et al [14], Borin et al [17], Simone et al [16], and Thyssen et al [19] recruited women above 18 years of age, whereas the study by Reis et al [13] involved also women aged below 18 years.…”
Section: Resultsmentioning
confidence: 99%
“…Women with UI feel ashamed and embarrassed to engage in various activities; it should be noted that urinary loss during sports practice involves one third of women and constitutes a social problem [19,29]. Therefore women adopt prevention strategies, such as the application of tampons during sports practice, lavatory use, and the reduction of liquid ingesting before exercises [18,19].…”
Section: Discussionmentioning
confidence: 99%
“…Por fim, Ferreira et al 2 incluíram em seu estudo experimental 32 jogadoras de vôlei de um clube profissional de Portugal. 16 mulheres foram incluídas no grupo experimental que se submeteu a três meses de treinamento com protocolo e receberam folheto educativo.…”
Section: Tratamento Das Disfunções Dos Mapunclassified
“…Diversos fatores podem influenciar o funcionamento correto dos músculos do assoalho pélvico (MAP) e a prática de exercícios físicos destaca-se entre eles 1,2 . A atividade física oferece muitos benefícios para a saúde, contudo, alguns autores afirmam que quando praticada de forma exorbitante, pode levar a disfunções tais como a incontinência urinária (IU) 1,2 .…”
Section: Introductionunclassified